HUBUNGAN KEMAMPUAN BERPIKIR KRITIS DENGAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV SDN TANGERANG 2 KOTA TANGERANG - Citra Septiliana; Moh Zamroni; Arry Patriasurya Azhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the relationship between critical thinking skills and understanding of mathematical concepts. This study uses a quantitative approach using a survey method used through SPSS statistics. The population in this study is grade IV students of SDN Tangerang 2 Tangerang City with a population of 58 students and a sample of 48 students. The sampling technique uses Simple Random Sampling. The research instruments carried out are questionnaires and test questions in the form of essays. The data collection instrument for critical thinking ability (variable X) uses a Likert Scale questionnaire with answer choices 1-5 and the understanding of mathematical concepts (variable Y) uses essays. The results of this study showed a significant relationship between critical thinking skills and understanding of mathematical concepts of grade IV students of SDN Tangerang 2 Tangerang City, with a pearson correlation value of 0.585 with a significant value of 0.001. Which means that if students' critical thinking skills are high, students' understanding of mathematical concepts will be better, and vice versa. This can be proven by the value of the determination coefficient, which is 34.2% and the remaining 65.8% is influenced by other factors.